Virtual learning and student's motivation: implementation the “game ranking 1st” through quizizz - Nurul Ahsin; Chintya Rahmawati (IAIN Salatiga, 2020)
The study focuses on the implementation of the “Game Ranking 1st” method to increase student learning motivation in the subject of Islamic Religious Education at SMPN 3, Pare, Kediri. Through this learning method, the online teaching and learning process is expected to be learner-centered, while the teacher acts as a guide. This study uses qualitative approaches and descriptive methods. Data Collection techniques through interviews, observation, and documentation. The informants involved in this study were a teacher of Islamic Religious Education and several students at grade VII of SMPN 3 Pare, Kediri. The result of this study indicates that: 1) The application of the “Game Ranking 1st” method in Islamic Education is implemented in stages; preparation, in the form of checking attendance and presenting learning steps; implementation, by providing the Quizizz web link along with the code to students; and evaluate learning outcomes. 2) Through the “Game Ranking 1st” method, student’s intrinsic motivation is increased marked by their enthusiasm and high interest in learning, along with extrinsic motivation, they are attracted by the stimulus provided by the teacher in the form of value rewards and praise, and punishment in the form of adding questions and assignment.